EFEITO DO ESTRESSE TÉRMICO SOB A PRODUÇÃO DE EMBRIÕES IN VITRO A PARTIR DE OÓCITOS BOS INDICU - Da Silva, Jéssica; Cáceres, Mirela; Da Silva, Ruan Francisco; Da Silva, Aldair Félix; Ortiz, Giovanna; Sterza, Fabiana (ANAIS DO ENIC, 2018)
-